Using socio-ecological model to inform the design of persuasive applications - Mohd Mohadis, Hazwani; Mohamad Ali, Nazlena (ACM, 2015)
Diverse persuasive applications that aim for behavioural changes have been developed. However, the method in which particular persuasive design principles are chosen over others remains unclear. Meanwhile, the use of socio-ecological model has been widely utilized in clinical research, as a basis to understand the factors in the entire ecological system that influences behavioural patterns. Because persuasive technology aims to change the behaviour and attitudes of users, we believe that the use of socio- ecological model would be beneficial to inform the design of persuasive applications. Accordingly, in this paper, we attempt to demonstrate the mapping of the socio-ecological factors and persuasive design principles by conducting interviews and expert reviews. Based on our approach, 12 socio-ecological factors that influence physical activity behaviour, and corresponding relevant persuasive design principles to deal with these factors, are identified.